Análise dos principais fatores relacionados à evolução e à resposta terapêutica no câncer de mama correlacionados aos desfechos clínicos em pacientes de um hospital universitário de referência - Freitas, Sabrina Ribas (2016)
This study aimed to describe the prognostic and predictive factors of breast cancer and the correlation between them with the clinical outcomes observed in patients surgically treated at the University Hospital of Santa Maria, from 1999 to 2009. The study was retrospective, observational , transversal and analytical. The data was obtained by reviewing the medical records of patients with the Medical Records and Statistics Service sector (SAME). Female patients with malignant pathology of the breast, without distant metastases at diagnosis, and treated surgically in HUSM were included in the sample. Patients with a diagnosis of carcinoma in situ of the breast, male patients, patients with metastases at the time of surgery, patients with other concomitant cancer, patients who had surgical treatment before 1999, patients less than 60 months of follow-up, patients transferred after treatment and patients diagnosed with malignant phyllodes tumor. In the period, 411 cases were identified, 136 of them being excluded. In total, 275 cases were included in the study, and the classification of molecular subtypes was performed in 185 cases. The results were: mean age at diagnosis of 53.13 years; average tumor size in pathology assessment of 2.91 cm; 86.18% type invasive ductal carcinoma; 57.45% histologic grade 2; 60 cases of pure luminal tumors and 196 patients in stages I and II (pathological staging); 205 patients presented with disease without activity; It was reported 45 deaths, and in 33 of them the cause was breast cancer. It was not possible to compare the most variables between the groups. Difference was observed between the groups in histological grade and KI-67. The development of a prospective study is suggested, with its own protocol, for proper description of these factors, which will analyze them and compare them among subgroups of patients. The effort to acknowledge the profile and development of malignant neoplasm of the breast can help individualize treatment, adjusting it for each case.